-4(4u-1)+4u=9+3(2u-5)

Simple and best practice solution for -4(4u-1)+4u=9+3(2u-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(4u-1)+4u=9+3(2u-5) equation:


Simplifying
-4(4u + -1) + 4u = 9 + 3(2u + -5)

Reorder the terms:
-4(-1 + 4u) + 4u = 9 + 3(2u + -5)
(-1 * -4 + 4u * -4) + 4u = 9 + 3(2u + -5)
(4 + -16u) + 4u = 9 + 3(2u + -5)

Combine like terms: -16u + 4u = -12u
4 + -12u = 9 + 3(2u + -5)

Reorder the terms:
4 + -12u = 9 + 3(-5 + 2u)
4 + -12u = 9 + (-5 * 3 + 2u * 3)
4 + -12u = 9 + (-15 + 6u)

Combine like terms: 9 + -15 = -6
4 + -12u = -6 + 6u

Solving
4 + -12u = -6 + 6u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-6u' to each side of the equation.
4 + -12u + -6u = -6 + 6u + -6u

Combine like terms: -12u + -6u = -18u
4 + -18u = -6 + 6u + -6u

Combine like terms: 6u + -6u = 0
4 + -18u = -6 + 0
4 + -18u = -6

Add '-4' to each side of the equation.
4 + -4 + -18u = -6 + -4

Combine like terms: 4 + -4 = 0
0 + -18u = -6 + -4
-18u = -6 + -4

Combine like terms: -6 + -4 = -10
-18u = -10

Divide each side by '-18'.
u = 0.5555555556

Simplifying
u = 0.5555555556

See similar equations:

| (-7x^2y)(-10x^3y^5)= | | 5b-20=15 | | 15q-14q=20 | | (-.75)(-8x)(1.3)(4y)(1)=c | | -3(d-7)+9=27 | | 2x^2+10-600=0 | | 2s+s=15 | | 3.6(x+9)+4.9x= | | -6=z/5-3 | | 14xy-35yz-63xz= | | 8c-4c=16 | | 2(3b-5)+6b=14 | | 1.6(x-5.5)=10.4 | | X(5+12)=52 | | x+3x+0=7x-15 | | -3y+8=14 | | 9(3x)=16 | | -2(a-2)+4=16 | | 8(3a-4)= | | -3n-8= | | 8x^4y+56x^2y^2-32x^2y= | | 1-9a=-15-2x | | -3(-5v+5)-v=4(v-2)-1 | | y=4/3x-2 | | 5/8y-8=8 | | -2(2p-1)-2(p-1)= | | -4(2X-3)+5X=33 | | 0.6x-13=2.2x-21 | | 4x-5=3(6+x)+6 | | 15+45-2x=15x+2x-5 | | 2x+37= | | 4(K+5)-20=28 |

Equations solver categories